A VOCALIZAÇÃO DA LATERAL PÓS-VOCÁLICA COMO FENÔMENO NEOGRAMÁTICO DO NÍVEL PÓS-LEXICAL - Costa, Cristine Ferreira (Organon, 2004)
In this paper, we examine the postlexical status of the process of vocalization of /l/ inBrazilian Portuguese. We present a characterization of this type of sound change based on statisticalresults taken from the quantitative analysis of spoken language. Our sample consists of 12 interviewsof people living in Porto Alegre. First, the geometrical representation of the lateral segment and ofthe process of vocalization is analyzed. Secondly, we discuss the lexical/postlexical status of thevocalization process according to the hypothesis of the Neogrammarian Controversy resolution asproposed in Labov (1981) and reworked in Kiparsky (1988) and Labov (1994). Finally, we alsodiscuss the opacity of the relationship between the processes of /l/ vocalization and ofmonophthongization of /ow/ diphthong.